TYPES OF HEMOLYSINS PRODUCED BY STAPHYLOCOCCUS AUREUS, AS DETERMINED BY THE REPLICA PLATING TECHNIQUE - Haque, Riaz-Ul (1964)
Haque, Riaz-Ul (The Ohio State University, Columbus), and Jack N. Baldwin. Types of hemolysins produced by Staphylococcus aureus as determined by the replica plating technique. J. Bacteriol. 88:1442–1447. 1964.—The type of hemolysins produced by a representative number of cells of a culture of Staphylococcus aureus was determined by the replica plating technique, with the use of sheep, rabbit, human, and horse blood agar plates. Unless horse and human red blood cells were used, a distinction between α-and δ-hemolysins was difficult to make. Strains producing α-β–, β-δ–, and α-δ–hemolysins were recognized by the replica plating technique. A few colonies produced lysis of rabbit, horse, and human cells without lysis of sheep red blood cells. This pattern of lysis was not detected by the radial streak or the tube titration procedures when mixed populations were examined, and may be due to a lytic factor not hitherto described.